Uterine cervix pre malignant lesions recurrence in patients treated with Leep conization - Rojas Clavijo, Leoyfred (2015)
Background: Cervical cancer ranks first in Peru and in developing countries and is the second leading cause of cancer death in women. Smear screening and treatment of early preinvasive lesions allow close to 100% cure. Objectives: To determine recurrence in patients with diagnosis of premalignant lesions treated with Leep conization. Design: Descriptive, retrospective study. Setting: Oncology Gynecology and Breast Service, Hospital Nacional Arzobispo Loayza, Lima, Peru. Participants: Patients with cervical epithelial neoplasia diagnosis treated with Leep conization. Interventions: The records of 74 patients with cervical epithelial neoplasia diagnosis treated with Leep conization during the period 2003-2007 were reviewed. Main outcome measures: Lesion recurrence. Results: From all patients studied, 13 (17,6%) had recurrence, mostly within the first two years. Conclusions: Recurrence of cervical epithelial neoplasia occurred was higher than in other reports. There was significant relationship between age at diagnosis, age at first intercourse and number of sexual partners. At the end of the study all patients were disease free.